2017
DOI: 10.1186/s12879-017-2421-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing tuberculosis management under public and private healthcare providers: Victoria, Australia, 2002–2015

Abstract: BackgroundPrivate healthcare providers are important to tuberculosis (TB) management globally, although internationally there are reports of suboptimal management and disparities in treatment commencement in the private sector. We compared the management of TB patients receiving private versus public healthcare in Victoria, an industrialised setting with low tuberculosis (TB) incidence.MethodsRetrospective cohort study: 2002–2015. Private healthcare provision was included as an independent variable in several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The median duration of delays found in this study align with those found in an international systematic review of the topic in 2009, which included 52 studies and found an average patient delay of 28.7 days and average health system delay of 25 days . Findings are also comparable to the latest studies conducted in Australia on this topic …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The median duration of delays found in this study align with those found in an international systematic review of the topic in 2009, which included 52 studies and found an average patient delay of 28.7 days and average health system delay of 25 days . Findings are also comparable to the latest studies conducted in Australia on this topic …”
Section: Discussionsupporting
confidence: 87%
“…The limitations of this study include its retrospective nature, making it vulnerable to recall bias, with data concerning primary outcomes based on hospital records of symptom onset and nature recorded by medical officers rather than directly from patients. It was also limited to a single centre, which raises the possibility that findings are specific for this site; however, it is reassuring that a similar duration of health system delay was found in the recently conducted study by Dale et al 13…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The Victorian Tuberculosis Program is the statewide authority responsible for TB public health management, including medication supply and contact tracing [ 12 ]. Notification of all cases of TB is compulsory in both public and private healthcare settings, with case management and outcome records maintained in a central existing electronic public health record system [ 13 ]. This system also includes laboratory diagnostic records, including molecular and phenotypic drug susceptibility testing results.…”
Section: Study Population and Methodsmentioning
confidence: 99%